Twenty-first-century children's gothic : from the wanderer to nomadic subject - Germaine Buckley, Chloé (Edinburgh University Press, 2018)
This is the first monograph that brings together the fields of Gothic Studies and children's fiction to analyse a range of popular and literary works for children published since 2000.